Synergistic Fire Retardancy of Bis(1-methoxy-2,2,6,6-tetramethylpiperidin-4-yl)sebacate and Tris(2,4,6-tribromophenoxy)-1,3,5-triazine/Sb2O3 in HIPS - Hongzhi Wu; Junhong Liu; Qi Zhang; Mingmei Sun; Jingwei Yang; Linsheng Tang (Advances in Materials Science and Engineering)
Bis(1-methoxy-2,2,6,6-tetramethylpiperidin-4-yl)sebacate (NORSM) was found to perform an exceptional synergistic effect with tris(2,4,6-tribromophenoxy)-1,3,5-triazine (TTBPC)/Sb2O3 in HIPS. The LOI of fire retardant HIPS (FR-HIPS) with 16 wt% of TTBPC/Sb2O3 increased from 23.8% to 25.2%, the flame retardant rating of FR-HIPS was improved from UL 94 V-2 to UL 94 V-0, and various heat release parameters such as peak heat release rate, total heat release, and mean effective heat of combustion were greatly lowered by combining NORSM of 0.50 wt%. The Py-GC/MS results revealed that NORSM induced the role of synergistic effect; the main mechanisms were as follows: the active radicals such as methoxy radicals and aminyl radicals produced by the pyrolysis of NORSM promote the release of bromine radicals from TTBPC and the formation of HBr and CO2, which improves the flame retardancy of TTBPC/Sb2O3; the above active radicals, together with HBr, quench active free radicals, such as the hydroxyl radical (OH), and decompose the free radical source, which interrupts the chain reaction during combustion and results in a more efficient flame retardant effect in gaseous phase.